1997
DOI: 10.1088/0022-3727/30/21/001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent thermal conductivity of porous silicon

Abstract: The thermal conductivity of electrochemically etched porous silicon (PS) layers was determined over a wide temperature range (T = 35 - 320 K) using the dynamic technique. Both the doping level of the silicon wafers (p and ) and the porosity P of the porous layers (P = 64 - 89%) were varied. The measured thermal conductivities were three to five orders of magnitude smaller than the values for bulk silicon. Furthermore, they increase with increasing the wafer doping level and with decreasing the porosity P of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
182
3
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 16 publications
16
182
3
3
Order By: Relevance
“…2 Effective thermal conductivity (Wm -1 K -1 ) as a function of porosity for pore radii of 2 (•), 5 (▲), 10 (■) and 100 (♦) nm. Comparison of the results of our model (solid lines) with reported experimental data [1,7] and, in dashed lines, the hydrodynamic model [8] (Fig. 2a) and the Lysenko model [23] (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…2 Effective thermal conductivity (Wm -1 K -1 ) as a function of porosity for pore radii of 2 (•), 5 (▲), 10 (■) and 100 (♦) nm. Comparison of the results of our model (solid lines) with reported experimental data [1,7] and, in dashed lines, the hydrodynamic model [8] (Fig. 2a) and the Lysenko model [23] (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…It is confirmed that the results provided by the Eucken, Sumirat and percolation models are rather far from the experimental data for all the ranges considered. A further comparison between EIT, the hydrodynamic model and experimental data [1,7,23] for several values of the pore radii ( = 2, 5, 10 and 100 nm) is found in Fig. 2(a).…”
Section: Results and Comparison With Other Modelsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the same work, the thermal conductivity of as-prepared meso-porous silicon (45% porosity) was measured to be 80 W/m K which dropped to 2.7 W/m K upon oxidation at 300 • C. Temperature dependent measurements in the range of 35 K-320 K using the 3ω method were first reported by Gesele et al 57 The thermal conductivities of all the investigated samples increased with increasing temperature, and were less than 1W/ m K at room temperature. A minimum value of 0.03 W/m K was reported for p-type porous silicon with 89% porosity and 4.5±0.6 nm crystallite size.…”
Section: Transport In Non-periodic Meso-and Nano-porous Structuresmentioning
confidence: 79%